PREVALENCE AND ANTIMICROBIAL SUSCEPTIBILITY OF METHICILLIN RESISTANCE STAPHYLOCOCCI ISOLATED IN A TERTIARY CARE HOSPITAL OF RURAL GUJARAT, INDIA - Trivedi, Artee A. Tyagi, Dr. Sunil S. (Journal of Biomedical and Pharmaceutical Research, 2017)
Antibiotic resistance, a global concern, is particularly emerging in developing nations, including India; where the burden of infectious disease is high and healthcare spending is low. Methicillin resistant S. aureus (MRSA) and Methicillin resistant coagulase negative Staphylococci (MRCoNS), are significant pathogens of concern causing both nosocomial and community acquired infections associated with increased morbidity and mortality. A prospective cross-sectional study was therefore conducted to determine the prevalence and antimicrobial sensitivity of Methicillin resistant Staphylococci isolated at Shree Krishna Hospital, Karamsad, Gujarat, India from June 2012 to August 2014. Identification and antimicrobial susceptibility testing (AST) were carried out by VITEK 2 Compact and the Methicillin resistance was confirmed by the modified Kirby Bauer Disc Diffusion method as per CLSI- 2012 guidelines. A total of 14,415 clinical specimens were processed, of which 707 Staphylococcal isolates were obtained. Among which, 362 (51.2%) were S. aureus and 345 (48.8%) were coagulase negative Staphylococci species. The prevalence of MRSA and MRCoNS were found to be 44.8% and 78.8% respectively. Methicillin resistant isolates showed high level of resistance to Penicillin followed by Erythromycin, Levofloxacin, Co-trimoxazole, Gentamicin and Clindamycin. Low level of resistance was seen against Vancomycin. Linezolid- resistant strain of Staphylococci was not found at all in the present study. Methicillin resistant strains showed higher antimicrobial resistance as compared with Methicillin sensitive strains. Thus, a continuous surveillance of Methicillin resistant Staphylococci (MRS) is essential for proper guidance of antimicrobial therapy and to minimize the irrational use of reserved antibiotics. Key words: MRSA, MRCoNS, Staphylococcal isolates, multidrug resistance, risk factors